Humanitarianism's Contested Culture in War Zones - Thomas G. Weiss (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2014)
Humanitarians are no longer simply seen as selfless angels. Their motivations and mastery, their principles and products are questioned from within and from without. Understanding the ongoing transformations in contemporary humanitarianism requires examining the nature and evolution of humanitarian culture away from an agreed culture of cooperation to a contested one of competition. The latter reflects militarization, politicization, and marketization. What is required is a learning culture for practitioners and a consequentialist ethics more oriented to responsible reflection than rapid reaction.
urn:nbn:de:hbz:464-20160128-085650-0
Keywords: 320; Humanitarianism; humanitarian business; ethics; marketization; militarization; international relations; globalization; development cooperation; global cooperation